On the Possibility of Intense Unipolar THz Pulses Formation in Nonhomogeneous Nonequilibrium Nitrogen Plasma Channels - Anna V. Bogatskaya; Ekaterina A. Volkova; Alexander M. Popov (Photonics, 2023)
We developed a 3D, fully self-consistent model for analysis of the ultrashort THz unipolar pulse formation accompanied by its amplification in a nonequilibrium plasma channel induced in nitrogen by a femtosecond UV laser pulse. The model is based on a self-consistent numerical solution of the second-order wave equation in cylindrical geometry and the kinetic Boltzmann equation for the electron velocity distribution function (EVDF) at different points of the spatially inhomogeneous nonequilibrium plasma channel. Rapid relaxation of the electron velocity distribution function in the plasma channel results in the amplification of the leading front of the THz pulse only, while its trailing edge is not amplified or even absorbed, which gives rise to the possibility of the formation of pulses with a high degree of unipolarity. The evolution of the unipolar pulse after its transfer from the channel to open free space is analyzed in detail.